Different distribution of adriamycin in normal and leukaemic rats. - Sonneveld, P. (Nature Publishing Group, 1981)
Adriamycin (ADR) accumulates in well-perfused organs in the rat. This effect is especially evident for long periods in marrow and spleen of healthy animals. In rats bearing the Brown Norway Acute Myeloid Leukaemia (BNML) the in vivo distribution is significantly different. Maximum ADR levels in those organs which are morphologically infiltrated by leukaemic cells are significantly lower than in normal rats, while the persistence of measurable ADR concentrations does not change. On the contrary, ADR concentrations in organs not infiltrated by leukaemic cells are the same or slightly higher than in normal rats. Possible causes for these differences are either the differential properties of normal and leukaemic cells in their uptake and excretion of ADR, or anatomical and vascular changes. It is evident that, significantly different from normal. This observation may help in the prevention of toxicity by drug monitoring in serum.